GENERAL TRADE PARTNERSHIP PERFORMANCE OF ALBASIA WOOD IN LEUWISADENG–BOGOR - Sarah Widyatami; Bambang Juanda; Trias Andati (Indonesian Journal of Business and Entrepreneurship (IJBE), 2016)
Difficulty in market information access, low prices and quality of farmers’ production, lack of facilities and infrastructure, needs of wood supply in a quick and large quantity have generated a partnership scheme which governs the farmers and industries to make a contract that binds and controls elements of production without having them. This study assessed the performance of partnership between a farmer group of “Binawarga Tani” and sawmills of UD Jaya Abadi, UD Dalfa Kamila, UD Putra Mandiri in Leuwisadeng, Bogor District. Comparative descriptive analysis states that partnership between the farmer group of "Binawarga Tani" and three sawmills has provided adequate results for both parties (mutual benefits) with an increase in the value of production and  sales better than conditions before the partnership. UD Jaya Abadi has had a strategy of product diversification and marketing that are not owned by the competitors. Partnership influences the value of cash inflows and is able to produce a surplus of cash for the actors of the partnership. Statistical analysis shows that the cash surplus of farmer group and three sawmills before and after the partnership is significantly different. The farmer group is able to achieve business efficiency with better break-even point each year. Financial performance of farmer group and partners has been improved with delta Net Present Value (NPV) of Rp14.589.233 for the farmer group, Rp88.599.757 for UD Jaya Abadi, Rp35.726.194 for UD Dalfa Kamila, and Rp96.738.609 for UD Putra Mandiri. The partnership has created business sustainability through the certainty of market and raw material supply. Keywords: trade partnership, farmer group, sawmill, financial performance